Aerodynamics characteristics estimation for wing-body combination of aircraft at supersonic speeds - 187883 Ong, Foong Keaw (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering (Aeronautic)) - Universiti Teknologi Malaysia, 2003